KEBIJAKAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENCEGAH PERILAKU BULLYING PADA SISWA DI MAN 2 ACEH BARAT - Marlina, Cut Nyak; Silahuddin; Zulfatmi (FITRAH: International Islamic Education Journal, 2023)
preventing bullying behavior among students at Senior High School 2 West Aceh. The research method used is descriptive qualitative with a case study approach. The informants for this research were five Islamic Religious Education teachers. The data collection technique uses interviews and documentation. The results of the research are that there are various policies implemented by Islamic Religious Education teachers to prevent bullying behavior among students at Senior High School 2 Aceh Barat, such as (1) instilling character values; (2) practice good morals; (3) provide a good example; (4) provide motivation and positive things; (5) educate about the impacts of bullying; (6) giving advice, creating mutual affection, respect and appreciation; (7) indoctrinating Islamic brotherhood; (8) providing attention; (9) does not differentiate between students; (10) taking an emotional approach, as well as; (11) cooperate or maintain active communication with students’ parents.